2018
DOI: 10.1002/2017jd027850
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Extreme Rainfall to Atmospheric Moisture Content in the Arid/Semiarid Southwestern United States: Implications for Probable Maximum Precipitation Estimates

Abstract: Sensitivity of extreme rainfall to atmospheric moisture content for the 19 August 2014 storm in Arizona is investigated based on numerical experiments using the Weather Research and Forecasting model. Analyses are designed to develop an improved understanding of the roles of atmospheric moisture content and complex terrain in controlling spatial and temporal variability of extreme rainfall in the arid/semiarid southwestern United States. The control simulation identifies complex interactions of low‐level moist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…There is a higher potential temperature and water vapor mixing ratio over the city during the second storm episode in the CTRL simulations as compared to the NoURBAN simulations (Figure S8). One of our previous studies shows monotonic increases of rain rates with atmospheric moisture content for the rainfall in the second storm episode of the 19 August 2014 storm (Yang & Smith, ).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…There is a higher potential temperature and water vapor mixing ratio over the city during the second storm episode in the CTRL simulations as compared to the NoURBAN simulations (Figure S8). One of our previous studies shows monotonic increases of rain rates with atmospheric moisture content for the rainfall in the second storm episode of the 19 August 2014 storm (Yang & Smith, ).…”
Section: Resultsmentioning
confidence: 82%
“…For CTRL and NoTOPO scenarios (two “urban” scenarios), we couple the single‐layer urban canopy model to accurately represent exchanges of heat, moisture and, momentum between the urban surfaces and lower atmosphere. An overview of WRF physics options adopted in all experiments is provided in Table S1 (also refer to Yang & Smith, , for details). Ensemble simulations are implemented through perturbations of initial conditions to increase the reliability of the results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the other BL schemes, the RRTM for global (RRTMG) scheme for shortwave and long‐wave scheme (Iacono et al ., ) is used. These model physics schemes have already been used in this region for difference studies (e.g., Bright and Mullen, ; Castro et al ., ; Newman and Johnson, ; Mahalov et al, ; Yang and Smith, ; Yang et al ., and Yang et al, ; and many others). The Noah land surface scheme with a single‐layer urban canopy (Chen and Dudhia, ; Kusaka and Kimura, ; Chen, ) is used in all runs.…”
Section: Methodsmentioning
confidence: 99%
“…Investigating the effects of Phoenix urbanization on extreme storm rainfall is critically important to urban flood warnings, to urban water resources management, and to urban expansion planning, substantially more important than investigating climatological averages. Yang and Smith () have investigated the effects of atmospheric moisture transport on storms that occurred north of Greater Phoenix using WRF at 1‐km resolution and concluded that the responses of storms to moisture are event‐dependent (time‐dependent). In the January 2019 American Meteorological annual meeting, Castro et al .…”
Section: Introductionmentioning
confidence: 99%